2021
DOI: 10.12933/therya-21-1117
|View full text |Cite
|
Sign up to set email alerts
|

On the utility of taxonomy to reflect biodiversity: the example of Lasiurini (Chiroptera: Vespertilionidae)

Abstract: The taxonomic history of bats of the tribe Lasiurini (Chiroptera: Vespertilionidae) has undergone significant changes over time. Authors at different times have recognized various numbers of genera and subgenera within the tribe. The most recent proposed change to generic level taxonomy (that there should be three genera recognized instead of a single genus) has been debated in the literature. We reviewed papers that commented on the recent changes to lasiurine generic taxonomy, as well as those that have adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Garbino (2015) and Garbino and Martins‐Junior (2018) proposed the use of subgenera to avoid change and maximize taxonomic stability. However, stable classifications are not the goal of phylogenetic systematics (Baird et al, 2022; Dominguez & Wheeler, 1997; Gaffney, 1979; Grant & Kluge, 2005; Isler et al, 2013; Kluge, 1989; Padial & De la Riva, 2006) and taxonomy must be constantly updated in the face of new data (Baird et al, 2022; Baker et al, 2021; Dominguez & Wheeler, 1997; Isler et al, 2013; Padial & De la Riva, 2006; Tello et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Garbino (2015) and Garbino and Martins‐Junior (2018) proposed the use of subgenera to avoid change and maximize taxonomic stability. However, stable classifications are not the goal of phylogenetic systematics (Baird et al, 2022; Dominguez & Wheeler, 1997; Gaffney, 1979; Grant & Kluge, 2005; Isler et al, 2013; Kluge, 1989; Padial & De la Riva, 2006) and taxonomy must be constantly updated in the face of new data (Baird et al, 2022; Baker et al, 2021; Dominguez & Wheeler, 1997; Isler et al, 2013; Padial & De la Riva, 2006; Tello et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The genus comprises small to medium-sized species with brightly coloured or banded dorsal pelage and a thickly furred dorsal uropatagium (Gardner and Handley 2008; Reid 2009 ). In recent years, Lasiurus has been separated into three distinct genera ( Baird et al 2015 , 2017 , 2021 ): Aeorestes Fitzinger, 1870, Dasypterus Peters, 1870, and Lasiurus ; however, currently Aeorestes and Dasypterus are considered to be subgenera ( Simmons and Cirranello 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Lasiurus includes the red, yellow, and hoary fur bats and is easily distinguished from other genera by its wide palatal emargination (approximately a third of the distance across the canines) that separates the premaxillae and upper incisors, and by its hairy uropatagium on its dorsal surface (Gardner and Handley 2008). Recently, Baird et al (2015Baird et al ( , 2017Baird et al ( , 2021 suggested the division of Lasiurus into three genera based on molecular data and external differences in fur colors: Lasiurus (red bats), Aeorestes (hoary bats), and Dasypterus (yellow bats). This taxonomic arrangement has been disputed by Ziegler et al (2016), Novaes et al (2018), and Teta (2019), citing a lack of support for this division in a monophyletic genus and stating that using subgeneric names preserves the nomenclatural stability and facilitates the searching in databases, especially when Aeorestes had never been used as a name for hoary bats.…”
Section: Introductionmentioning
confidence: 99%